A Ti-Fe-Sn thin film assembly for joining tungsten and reduced activation ferritic-martensitic steels. (5th July 2017) - Zhu, Wen; Qiang, Jianbing; Wang, Yingmin; Sun, Jizhong; Wang, Jianbao; Lian, Youyun; Feng, Fan; Liu, Xiang
Abstract: The effective joining of tungsten and reduced activation ferritic-martensitic (RAFM) steels is crucial to fabrication of the divertor components of fusion reactors. In the present work, a low neutron-activation filler metal system of Ti-Fe-Sn was designed to realize the so-called exothermic-reaction-assisted brazing. A series of three-layered Ti-Fe-Sn thin film assemblies were made by electroplating, which allowed the brazing of tungsten with a CLF-1 RAFM steel to be carried out at a temperature as low as 1090 °C. The joint structures made from the Sn-bearing filler metals demonstrated high strength and high resistance against thermocycling. The Sn-film layer in the filler assembly has delivered favorable alloying effects on depressing separation of Ti element in the W grain boundaries and the formation of pores, and on microstructure refinement in the brazed joints as well. Graphical abstract: Highlights: A Ti-Fe-Sn thin film assembly was designed for brazing W and reduced activation ferritic/martensitic steels. W/steel joints free of pores and cracks were obtained by vacuum brazing at 1090 °C. The W/steel joints demonstrated high strength and high thermocycling stability. The presence of Sn in the brazed joints depressed the formation of defects and resulted in microstructure refinement.